GEOTECHNOLOGIES APPLIED IN THE CONFLICTS OF LAND USE IN PERMANENT PRESERVATION AREAS IN THE MUNICIPALITY OF BARRA BONITA/SP - Campos, M.; Campos, S.; Campos, M. (Revista Brasileira de Engenharia de Biossistemas, 2020)
Conflict areas are defined by the misuse of land by man and have been causing serious problems to the environment, resulting in ecological imbalance and wear and tear on natural resources, especially when referring to permanent preservation areas, which are of fundamental importance for ecosystems in balance and preservation of water resources. Planning is a key factor in controlling environmental impacts on the environment. The areas of permanent preservation prevent silting and erosion, providing natural protection, especially in spring areas. The environmental services provided assist in the protection of flora and fauna, in the preservation of ecological corridors, and in the continuation of the species present there. This study aimed to evaluate the conflicts of land use and occupation in Permanent Preservation areas of the municipality of Barra Bonita / SP, using the Geographic Information System (GIS) and Sentinel 2-A satellite image of 2017 as a cartographic base, on a 1: 10,000 scale. The results showed that almost ¾ of the area is occupied by sugarcane (72.72%) and that the permanent preservation areas are being used inappropriately by sugarcane (72.75%). The GIS ArcGis and geoprocessing techniques demonstrated agility and efficiency in the identification, quantification and editing of land use maps, permanent preservation and conflicts in permanent preservation areas.